Steatotic liver disease diagnosed in a 24-year-old woman with Rett syndrome: a case report - Larissa Albino; Adil Adatia; Aducio Thiesen; Brendan Halloran; Victor Dong; Carlos Moctezuma-Velázquez (Journal of International Medical Research)
Rett syndrome (RTT) is a neurodevelopmental disorder caused by mutations in the MECP2 gene, potentially disrupting lipid metabolism and leading to dyslipidemia (DLD) and steatotic liver disease (SLD). Although SLD has been described in RTT mouse models, it remains undocumented in humans. We herein describe a 24-year-old woman with RTT who was evaluated for abnormal liver enzymes. Imaging revealed hepatic steatosis, and transient elastography showed a controlled attenuation parameter of 342 dB/m and stiffness of 7.1 kPa. Laboratory investigations excluded secondary causes, including insulin resistance, metabolic syndrome, alcohol use, and new medications. Her Homeostatic Model Assessment for Insulin Resistance score was 1.8, her hemoglobin A1c concentration was 4.8%, and her lipid profile showed elevated triglycerides and low-density lipoprotein, consistent with DLD. Liver biopsy confirmed SLD. This case supports the hypothesis that MECP2 mutations in RTT disrupt lipid metabolism through a unique pathophysiologic mechanism, increasing the risk of DLD and SLD independently of traditional metabolic syndrome factors. It highlights the importance of early screening for liver disease in patients with RTT, despite their young age, to prevent complications. Additionally, it validates MECP2 -null mouse models as reliable tools for investigating future therapeutic strategies in RTT.